A Little Magazine Called Mak. In the Periphery of the Revolution - Kromann, Thomas Hvid (Nordlit, 2007)
The Danish avant-garde magazine Mak contained throughout its short life an extensive discussion on whether or not art could be used as a weapon in the struggle for the new society the counterculture was dreaming about in the late nineteen sixties. Mak was devoted to this question: How can art move from the (aesthetic) periphery to the centre of (political) influence?